THE EFFECTIVENESS OF VILLAGE FUND MANAGEMENT IN IMPROVING BUMDES BUSINESS PERFORMANCE (Case Study in Limehu Village, Tabongo District, Gorontalo Regency) - Yayu Afriani Ekaputri R. Sidiki; Rio Monoarfa; Surya Handrisusanto Ahmad (PT. Jurnal Center Indonesia Publisher, 2026)
This research aims to determine the effectiveness of Village Fund management in improving the business performance of the Village-Owned Enterprise (BUMDes) in Limehu Village, Tabongo District, Gorontalo Regency. The study was motivated by the stagnant condition of BUMDes Sinar Utara despite the village receiving an annual Village Fund allocation. This research used a qualitative descriptive method with a case study design. Data were collected through in-depth interviews with six informants, document review, and direct observation, then analyzed using the Miles and Huberman interactive model and validated through triangulation. The results show that among the five dimensions of Village Fund management analyzed based on Minister of Finance Regulation (PMK) Number 145 of 2023, the dimensions of administration and fund utilization have run relatively effectively, while the accountability dimension has only been fulfilled procedurally, the reporting dimension has not been consolidated, and the monitoring and evaluation dimension remains reactive. Overall, Village Fund management in Limehu Village has not been optimal in improving the business performance of BUMDes Sinar Utara.